PDGFRA Immunohistochemistry Predicts PDGFRA Mutations in Gastrointestinal Stromal Tumors. (January 2022) - Papke, David J.; Forgó, Erna; Charville, Gregory W.; Hornick, Jason L.
Abstract : Platelet-derived growth factor receptor A (PDGFRA) is a receptor tyrosine kinase that is activated by mutations in 10% of gastrointestinal stromal tumors (GISTs) and 55% to 70% of inflammatory fibroid polyps. PDGFRA -mutant GISTs are usually epithelioid and occur predominantly in the stomach. Succinate dehydrogenase–deficient GISTs also arise in the stomach and are usually epithelioid, as are some KIT -mutant GISTs. Recently, avapritinib was approved to treat PDGFRA D842V-mutant GISTs, which do not respond to conventional targeted therapy. Here, we evaluate the utility of PDGFRA immunohistochemistry (IHC) to predict PDGFRA mutations to direct targeted therapy. PDGFRA IHC was performed at 1:3000 and 1:10, 000 dilutions on a tissue microarray containing 153 GISTs (126 KIT -mutant, 17 PDGFRA -mutant, and 10 succinate dehydrogenase–deficient). The "positive" staining threshold was defined as 50% of neoplastic cells staining at moderate intensity. PDGFRA IHC was 75.0% and 80.9% specific for PDGFRA mutations at 1:3000 and 1:10, 000 dilutions, respectively, and it was 100% sensitive at both. On the basis of its higher specificity, a 1:10, 000 dilution was used to stain whole-tissue sections of GISTs and other gastric tumor types. Combining tissue microarray and whole-tissue data, PDGFRA IHC was 94.4% sensitive and 81.0% specific for PDGFRA -mutant GIST among all 210 GISTs, and it was 84.1% specific among 149 GISTs with an epithelioid component. PDGFRA was positive in a subset of inflammatory fibroid polyps (15/30; 50%), monophasic synovial sarcomas (5/10; 50%), inflammatory myofibroblastic tumors (5/10; 50%), and plexiform fibromyxomas (2/8; 25%). It was negative in poorly differentiated adenocarcinoma (0/20), diffuse large B-cell lymphoma (0/10), glomus tumor (0/10), gastrointestinal neuroectodermal tumor (0/10), leiomyoma (0/10), gastric schwannoma (0/8), and gastroblastoma (0/3). Among GISTs, PDGFRA IHC is highly sensitive and moderately specific for PDGFRA -mutant tumors; it also can be positive in inflammatory fibroid polyp and some other mesenchymal tumor types. PDGFRA positivity could be used to triage epithelioid GISTs for PDGFRA sequencing to determine optimal therapy.